Aplicação da metodologia de análise de falhas com base na manutenção centrada em confiabilidade: um estudo de caso - Martim, Flávio Luiz (2019)
The contemporary intermodal logistics, especially at the railway phase, needs to operate within pre-established limits, parameters and targets, in order to maintain low costs to make the business viable, and also to ensure the availability and reliability of the company’s assets to achieve the high agility and complexity that is demanded for this operation. The Failure Analisys, based on the Reliability-Centered Maintenance (RCM), is a technique that can help organizations to develop a systematic improvement program, effectively achieving cost-effectiveness goals. The main purpose of the present case study is to use RCM implementation concepts and tools, particularly from the Failure Analysis steps, to initiate the implementation of this type of methodology in a company of the aforementioned branch, more specifically in an equipment known as Rail Mounted Gantry (RMG), used to move and stack containers, which is located in a rail terminal plant. Among the stages of the study, is had: i) the formation of the project group; ii) the selection of the system in which the method and its subsystems will be applied; iii) the analysis of the functions of the system and its functional failures; iv) the definition of critical items and; v) the analysis of failure modes and effects (FMEA application). With these analyzes, is aimed a high level of detail mapping that can be used in the future to develop equipment risk assessments, in addition to developing more robust and efficient maintenance plans, and well-funded realiability studies (not available until then in the company portrayed in the case study).